2017
DOI: 10.17977/um030v5i22017p076
|View full text |Cite
|
Sign up to set email alerts
|

Efl Students’ Preferences for Oral Corrective Feedback in Speaking Instruction

Abstract: This study investigates Indonesian EFL learners' corrective feedback preferences including the timing, types of error, strategies of corrective feedback, and providers of error correction; and the relationship between foreign language anxiety and preferences for corrective feedback among students. Two hundred fifty seven EFL English department undergraduate students from two different course grades participated in the survey. The data were collected through questionnaire as the main data and interview as the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…Park (2010) also selects 51 college students of different universities for the subjects of his research. Another research conducted by Fadilah (2016) also studies the students at the university level. These are some studies showing that mostly the research studies students from higher education level as the concern of the research.…”
Section: Jannah Furaidah Rachmajanti Elementary Efl Students'… 461mentioning
confidence: 99%
“…Park (2010) also selects 51 college students of different universities for the subjects of his research. Another research conducted by Fadilah (2016) also studies the students at the university level. These are some studies showing that mostly the research studies students from higher education level as the concern of the research.…”
Section: Jannah Furaidah Rachmajanti Elementary Efl Students'… 461mentioning
confidence: 99%
“…Foreign language teachers have relied on the notion of 'Oral Corrective Feedback' (henceforth, OCF) for the last two decades as it serves as a powerful remedy for leading learners to notice the incorrect language form and then to correct it (Fadilah et al, 2017;Park, 2010;Russel, 2009;Zhang & Rasimi, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, many studies have suggested that supporting learners with various corrective feedback might help them acquire the correct form as they are actively participating in the learning process. Therefore, the lack of corrective feedback might lead to fossilized errors as learners would assume their statements are correct (Fadilah, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Interaction plays an important role in a university lecture, especially in English department in Indonesia where literature is taught using English (Fadilah et al, 2017). In literature university lecture, interaction normally takes place between lecturer and students.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, students find that literature lectures are challenging for non-native speakers (NNS) of English as they have to successfully complete tasks given and to communicate with each other, besides receiving and sending comprehensible literature content knowledge from and to their lecturers (Rido & Sari, 2018;Rido et al, 2017;Shi, 2013). As these students are prepared to be a competent English communicator; therefore, lecturers must be aware of students' language competence and performance as well as enable them improving their literary knowledge (Fadilah et al, 2017;Lacia et al, 2019). Thus, repair strategies are needed to identify all aspects of the possible problems and to correct the wrong linguistic and content aspects produced since they cover a wide range of actions such as problems of hearing and understanding talk, prompting, cluing and helping, understanding, explaining, and correcting errors (Rido & Wahyudin, 2020;Rido, 2019;Li & Wang, 2018;Seong, 2006).…”
Section: Introductionmentioning
confidence: 99%